Desarrollo psicomotor en estudiantes de 4 años de una institución educativa inicial de Carmen de La Legua y Reynoso - Aguinaga Espinoza, Elízabeth Sophia (2012)
This descriptive investigation aims to describe the psychomotor level of development of 4 year-old students. The sample were 48 students male and female whose ages were 4 years 0 months – 4 years 11 month old that belonged to the morning shift of a preschool in Carmen de la Legua y Reynoso. The Test of Psychomotor Development (TEPSI) was used, adapted by Aguinaga and Aguinaga (2011). The results showed that the highest percentage of students is at a normal level, the psychomotor development is according to their chronological age.